Roles of dynein and dynactin in early endosome dynamics revealed using automated tracking and global analysis. - Neftali Flores-Rodriguez; Salman S Rogers; David A Kenwright; Thomas A Waigh; Philip G Woodman; Victoria J Allan (PLoS ONE)
Microtubule-dependent movement is crucial for the spatial organization of endosomes in most eukaryotes, but as yet there has been no systematic analysis of how a particular microtubule motor contributes to early endosome dynamics. Here we tracked early endosomes labeled with GFP-Rab5 on the nanometer scale, and combined this with global, first passage probability (FPP) analysis to provide an unbiased description of how the minus-end microtubule motor, cytoplasmic dynein, supports endosome motility. Dynein contributes to short-range endosome movement, but in particular drives 85-98% of long, inward translocations. For these, it requires an intact dynactin complex to allow membrane-bound p150(Glued) to activate dynein, since p50 over-expression, which disrupts the dynactin complex, inhibits inward movement even though dynein and p150(Glued) remain membrane-bound. Long dynein-dependent movements occur via bursts at up to ∼8 µms(-1) that are linked by changes in rate or pauses. These peak speeds during rapid inward endosome movement are still seen when cellular dynein levels are 50-fold reduced by RNAi knock-down of dynein heavy chain, while the number of movements is reduced 5-fold. Altogether, these findings identify how dynein helps define the dynamics of early endosomes.